Ethyl 4-amino-3-methylbenzoate - Song, Wen-Lan (International Union of Crystallography, 2008)
The asymmetric unit of the title compound, C(10)H(13)NO(2), contains two molecules which are linked via an N—H⋯N hydrogen bonds to form a dimer. These dimers are further linked via N—H⋯O intermolecular hydrogen bonds.